INTERNET SERVICES CAMPAIGN RANKING BASED ON AN INTEGRATED DECISION MAKING APPROACH - (:unkn) unknown (YILDIZ TECHNICAL UNIV, 2017)
Regarding the firms, the internet service sector in Turkey is quite small. There are few major brands competing strictly both to attract new customers and protect existing customers by providing advantageous and aggressive campaigns. In this study, a campaign selection model in the internet service sector is established by using multiple-criteria decision making techniques. While creating this model, it is benefited from the campaign information of Turkey's leading internet service provider. Besides, while determining the criteria and selecting alternatives, the opinions of experts were received. For determining criteria weights, AHP was used together with fuzzy approximations. For decision makers, there is always an environment of uncertainty in question and this uncertainty has been reduced to a minimum level with fuzzy logic. Later, within the scope of multi-criteria decision making techniques, the popular methods; TOPSIS and VIKOR were separately used to list the alternatives. Afterwards, one listing has been established by integrating two separate listings.
Keywords: FAHP; TOPSIS; VIKOR; internet services; FUZZY-AHP; PERFORMANCE EVALUATION; SYSTEM SELECTION; MCDM METHODS; VIKOR METHOD; TOPSIS; ENVIRONMENTS; METHODOLOGY; FIRMS; AREAS